Efecto de la salinidad en la tasa de reducción de amonio aplicando zeolitas comerciales - Aguilar Añazco, Viviana María (2014)
Ecuador is the first shrimp producer in Latin America, being able to produce shrimps all year round under controlled and sustainable conditions. Water quality parameters are essential for the culture management, especially keeping under control certain toxic metabolites that may harm the culture animals, such as ammonium/ammonia (NH4/NH3), which can be very harmful to the shrimp and can cause poor growth or even mortality, reason why it is advisable to maintain a NH3 concentration lower than 0.05 ppm. In the market there are various products to reduce or remove ammonium, such as: bacteria (under the nitrification process), formalin, Yucca schidigera extract, and minerals (zeolites). Zeolites have been used traditionally by farmers in order to reduce the NH4/NH3 present in the ponds, which are found in different presentations and quality, although its effectiveness in reducing TAN is ambiguous when exposed to high salinity levels. This research evaluated the effect of three commercial zeolites (A, B, C) at different weights (0.01 - 0.03-0.06 g) in reducing ammonia (0 - 0.3 – 0.6 - 1.0 ppm), under the effect of different salinities (6, 10, 15 ppt). Each treatment was in triplicate using 125 ml vials. Phenol method for the determination of ammonia was used. The TAN concentration was measured every 3 hours, for 24 hours. The results showed that the rate of TAN reduction varied based on the type of zeolite used and the salinity at which it was exposed, showing a TAN reduction ranging from 29.3 to 34.8 %, 30.3 to 37.4 % and from 32.0 to 37.1 % for the zeolite A, B and C, respectively. It was noted that an increase in salinity (6 ppt to 15 ppt) directly affected in a 4-7% in the TAN reduction observed. Additionally, the TAN reduction rate is not related to the amount of zeolite applied, but it was inversely proportional to the salinity being used. Taking into account the preceding paragraph it can be concluded that the zeolites used in the present study (A, B and C) responded in the same way, and therefore could be used at the lowest dose in the field, and thus reducing expenses during the growing season.